Perception and Socialization to Students about the MBKM Program at Study Program Technology and Management of Planation Production, IPB University - Wiraguna*, Edi; Pratama, Agief Julio; Rochmah, Hidayati Fatchur (Riwayat: Educational Journal of History and Humanities, 2024)
The Indonesian government launched the Merdeka Belajar Kampus Merdeka (MBKM) program to provide higher education that is more inclusive, flexible and relevant for students in 2019. However, there are indications that students still need to understand the implementation and procedures of the MBKM. This research aims to determine perceptions of knowledge, implementation and student evaluation of MBKM. Survey activities were carried out by collecting descriptive data from active students with statement criteria of 4 scales (strongly agree, agree, disagree and disagree). More than 95% of the respondents strongly agreed and agreed with implementing MBKM. However, the survey results show that socialization regarding the MBKM program is needed. After conducting socialization of the same respondents, all respondents stated that they strongly agreed with the MBKM program and that the registration process and guidance for the MBKM program had been well carried out.